Answer:
So Imma use the explanation area to answer this (I'll link a video on how I solved this.)
Explanation:
F(x)=1/3(-5x -4)³-3 (Multiply 1/3 by -5x & -4. Be sure to move the unused parts of the equation down)
F(x)= -1.66x -1.33³-3 (Here we need to use our exponent)
F(x)= -1.66x -2.37 -3 (Here we need to subtract -3 from -2.37)
F(x)= -1.66x - 0.629 (You need to subtract 0.629 from the right side and left side)
-0.629 = -1.66x (Now since X is attached by multiplication, we need to divide both sides by -1.66)
0.378 = x (this means that your inverse is 0.378)